Medical Ethics & Humanities Curriculum, Years I And II Medical Students - Liva Jacoby (Association of American Medical Colleges, 2009)
Abstract This resource discusses medical ethics humanities curriculum first- and second-year medical students at Albany Medical College. The multi-disciplinary curriculum describes a series of group sessions that were held over the course of the scholastic year. The overall goal was to promote an understanding of the complexities of the physician-patient relationship in today's health care environment. It addresses the notion of the "art of medicine" as a complement to the science of medicine, and examined topics related to professionalism, medical ethical principles, communication, and broader concerns related to the physician-patient relationship and bioethics. Students that underwent the curriculum responded with positive feedback. Application of skills and knowledge has also been observed during clinical years.